ENGLISH AND UZBEK INTERPRETATIONS OF ZOOSEMISM IN PROVERBS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
Each nation has proverbs based on their experience.In this article English and Uzbek proverbs are analyzed.